Weldability of welded joint alloy steel grade 91 to stainless steel grade 316L using filler metal ER NiCrMo-3 and ER 309LMo in power boiler piping and tubing - Kurniyanto, Hendri Budi; Rohmat, Imam Khoirul; Muh Sulhan, Ilham Ainur Rosyid; Marzuki, Marzuki (Politeknik Negeri Lhokseumawe, 2024)
Welded joints between high alloy steel and austenitic stainless steel are commonly used in the power plant industry. In this research, the materials used were SA-335 P91 and 316L stainless steel with ERNiCrMo-3 and 309LMo fillers designed with a butt joint configuration. Several mechanical test (tensile test ASTM E8, Hardness Test ASTM E92) and microstructure examination was carried out to determine the tensile strength, hardness and microstructure of welded joint. The highest tensile strength is found in the ERNiCrMo-3 filler metal, namely 354.085 MPa, while the lowest is found in the 309LMo filler metal, namely 349.87 MPa. The highest hardness values for the ERNiCrMo-3 filler metal are found in base metal P91, HAZ P91, weld metal, HAZ stainless steel 316L, and base metal stainless steel 316L, with values respectively 212.77 HVN, 278 HVN, 239.53 HVN , 189.32 HVN, and 180.40 HVN. The lowest values for the 309LMo filler metal are 210.13 HVN, 266.12 HVN, 206.48 HVN, 175.59 HVN, and 172.32 HVN. Microstructural observations show the formation of a dendrite phase in the weld metal area with ERNiCrMo-3 filler metal and a delta ferrite phase in the weld metal area with 309LMo filler metal. No phase changes were observed in the P91 base metal, P91 HAZ, 316L stainless steel base metal, or 316L stainless steel HAZ areas. The results of the corrosion resistance test show that specimens with the ERNiCrMo-3 filler metal are more resistant to pitting corrosion compared to specimens with the 309LMo filler metal. The corrosion rate is 12,50 mm/years for ERNiCrMo-3, and 18,94 mm/years for 309LMo filler metal.